Modulation of Cav3.2 T-type calcium channel permeability by asparagine-linked glycosylation - Ondacova, Katarina; Karmazinova, Maria; Lazniewska, Joanna; Weiss, Norbert; Lacinova, Lubica (Channels (Austin, Tex.), 2016)
Low-voltage-gated T-type calcium channels are expressed throughout the nervous system where they play an essential role in shaping neuronal excitability. Defects in T-type channel expression have been linked to various neuronal disorders including neuropathic pain and epilepsy. Currently, little is known about the cellular mechanisms controlling the expression and function of T-type channels. Asparagine-linked glycosylation has recently emerged as an essential signaling pathway by which the cellular environment can control expression of T-type channels. However, the role of N-glycans in the conducting function of T-type channels remains elusive. In the present study, we used human Cav3.2 glycosylation-deficient channels to assess the role of N-glycosylation on the gating of the channel. Patch-clamp recordings of gating currents revealed that N-glycans attached to hCav3.2 channels have a minimal effect on the functioning of the channel voltage-sensor. In contrast, N-glycosylation on specific asparagine residues may have an essential role in the conducting function of the channel by enhancing the channel permeability and / or the pore opening of the channel. Our data suggest that modulation of N-linked glycosylation of hCav3.2 channels may play an important physiological role, and could also support the alteration of T-type currents observed in disease states.
Keywords: Ion Channel Gating; Calcium Channels, T-Type; permeabilita; glycosylation; HEK293 buňky; vápníkové kanály - typ T; gating iontového kanálu; Cav3.2; HEK293 Cells; calcium channel; Asparagine; Permeability; gating; lidé; Humans; elektrofyziologické jevy; Electrophysiological Phenomena; glykosylace; T-type channel; Glycosylation; asparagin